2019
DOI: 10.1186/s12961-018-0399-5
|View full text |Cite
|
Sign up to set email alerts
|

The challenges of implementation of clinical governance in Iran: a meta-synthesis of qualitative studies

Abstract: BackgroundPolicy- and decision-makers seek to improve the quality of care in the health sector and therefore aim to improve quality through appropriate policies. Higher quality of care will satisfy service providers and the public, reduce costs, increase productivity, and lead to better organisational performance. Clinical governance is a method through which management can be improved and made more accountable, and leads to the provision of better quality of care. In November 2009, the Iranian Ministry of Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Our findings suggest that, to date, progress toward a comprehensive approach in the implementation of CDSM has been limited. Most of the reviewed articles investigated studied single chronic diseases and yet their conclusions on how such findings would promote the adoption of patient-centered models in the Iranian health system were limited (Behzadifar et al, 2019). We have identified three main areas that CDSM in Iran could facilitate such patient-centered approach and help the Iranian health system benefit from the positive outcomes that are associated with the CCM.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that, to date, progress toward a comprehensive approach in the implementation of CDSM has been limited. Most of the reviewed articles investigated studied single chronic diseases and yet their conclusions on how such findings would promote the adoption of patient-centered models in the Iranian health system were limited (Behzadifar et al, 2019). We have identified three main areas that CDSM in Iran could facilitate such patient-centered approach and help the Iranian health system benefit from the positive outcomes that are associated with the CCM.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have not reported patient SDM to be favorable (9)(10)(11)(12)(13). Moreover, the level of health literacy, knowledge, and education, type of decision-making required, type of disease, gender, age, race, economic and social status, and the use of medical alternatives are among the effective factors in the SDM of patients (5,11,(14)(15)(16).…”
Section: Introductionmentioning
confidence: 95%
“…In this system, patient centralism is essential to provide quality services that meet the desired standards. In this respect, patient rights are one of the most important axes of clinical governance (13). Factors related to SDM levels can vary in different cultures and communities (17).…”
Section: Introductionmentioning
confidence: 99%
“…In this system, patient centralism is essential to provide quality services that meet the desired standards. In this respect, the patient rights is one of the most important axes of clinical governance (13). Factors related to SDM levels in different cultures and communities can vary (17).…”
Section: Introductionmentioning
confidence: 99%